Platypnea-orthodeoxia syndrome in COVID-19: rare, not uncommon - Renu Kumawat; Mahesh Lal; Jagadeesan S.; Prarit Varshney (The Egyptian Journal of Bronchology, 2022)
Abstract COVID-19 is a contagious disease caused by the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). As humanity continues to fight this virus, it keeps presenting with new manifestations and complications. Platypnea-orthodeoxia syndrome (POS) is a rare clinical syndrome characterized by dyspnea and oxygen desaturation, in the supine to sitting position, which resolves with recumbency and can be diagnosed with a simple pulse oximeter. We report three cases of COVID-19 pneumonia, who developed POS during the recovery phase, in the absence of pulmonary hypertension.